THE NATURE OF THE AUTHORITIES IN A DEMOCRATIC RULE OF LAW - Shandi Patria Airlangga (Cepalo, 2019)
The Government should have the ability to regulate the people. The policy of a ruler is firm, not blunt up and sharp down. The state in principle is not based on mere power (matchtsstaat), but is also based on law. In the rule of law, a rule of law is not created for bad purposes. Monocracy and democracy can live and grow in harmony with one another. The rule of law cannot be established without democratic government, and democratic rule without law will become anarchist. Legal development is carried out through a process of nomocracy and democracy at the same time. The government as the people's representative creates a legal politics that favor the people's interests. The consequence of the concept of a democratic state is to mix all members of society and force them to live together. Power tends to make the government forget itself and lose its ethics as a person assigned by the people to take care of the country. To change the misguided paradigm of the government, a vertical and horizontal relationship between the government and the people was applied. Government with its function as the holder of power should be able to align the interests of the people with their interests. Thus the dream of creating a unitary and prosperous state that is just and civilized is truly realized. The creation of a good reciprocal relationship will not be realized if the government is not on the right path.